A COAGULATION-FLOCCULATION PROCESS COMBINED WITH ADSORPTION USING ACTIVATED CARBON OBTAINED FROM SLUDGE FOR DYE REMOVAL FROM TANNERY WASTEWATER - Mayerly J. Puchana-Rosero; Eder C. Lima; Bianca Mella; Dimitrius Da Costa; Eduardo Poll; Mariliz Gutterres (Journal of the Chilean Chemical Society, 2018)
Coagulation-flocculation (CF) process studies on aqueous solutions of Acid Black 210 dye (AB-210), were performed to investigate efficiency at different pH, coagulant and polyelectrolyte doses, and sedimentation times. In the adsorption studies of the dye removal, the initial pH and isotherms studies were performed using an activated carbon prepared by microwave-assisted pyrolysis of Tannery sludge. This adsorbent material was characterized by isotherms of N2 adsorption-desorption and density functional theory. Finally, the efficiency of the combined process CF followed by adsorption, was shown using a synthetic effluent identical to that produced in the wet-end process of the leather industry in industrial equipment. Effluent was collected from each treatment bath and analyzed for its physical properties and by ion chromatography. The best conditions found in CF processes were: pH 10.0, sedimentation time of 60 minutes, coagulant dose of 71 mg L-1 (Al2(SO4)3) and dose of flocculant (polyelectrolyte FX AS1) of 0.090 mg L-1. In the adsorption processes, the equilibrium data were best fit to the Liu isotherm model, presenting the maximum sorption capacity (Qmax) for AB-210 of 974.7 mg g-1 at 303.15K at pH 2.0. Using the synthetic effluent, the combined CF followed by adsorption of AB-210 dye demonstrated a removal of 85.2%, indicating that the combined process is efficient for real wastewater treatment.